Systematic Review of GC-MS-Based Methods for Determination of Aldehydes in Electronic Cigarette Liquids - Ismatun Wafiyah; Mochammad Yuwono; Riesta Primaharinastiti (Dinasti Research, 2026)
Electronic cigarettes generate toxic aldehyde compounds through the thermal decomposition of primary e-liquid constituents, namely propylene glycol and glycerol, yet standardized analytical methodologies for their determination remain critically fragmented across research institutions worldwide. This study conducted a systematic literature review adhering to the PRISMA 2020 protocol, encompassing 15 peer-reviewed articles retrieved from PubMed, Scopus, and Web of Science covering the period 2016 to 2024, specifically examining GC-MS-based methods for aldehyde determination in e-liquid matrices. Comparative synthesis demonstrated that headspace GC-MS incorporating isotopic internal standards constitutes the most robust analytical approach, consistently achieving linearity coefficients exceeding R²>0.990 without the requirement for chemical derivatization. Formaldehyde, acetaldehyde, and acrolein were recurrently identified as predominant aldehydes, with emission intensities exhibiting strong positive correlation with device operational parameters including voltage and heating power. Detection of formaldehyde-hemiacetal revealed substantial underestimation inherent to conventional measurement approaches regarding total aldehyde exposure. Pronounced methodological fragmentation across laboratories and the absence of matrix-specific certified reference materials represent principal barriers to global interlaboratory data harmonization. Standardization of reference methods through international interlaboratory collaboration is critically recommended to ensure robust and effective safety surveillance of electronic cigarette products.